The Consumer Perception towards Online Shopping Loyalty in Malaysia - Cheong, Jia Cheng (2013)
There are about 2 billion internet users around the world. Internet has transformed the ways we live and the ways we work and the way we practice. Among the e-commerce, online shopping is a potential and growing industry in almost every nation. For example countries such as United States, China, England, and Japan, they have their famous and representatives online shopping portal with huge earning. For example the famous website in US is Amazon, China is the Taobao.com etc. Those website famous not only in own countries but also in international market as well. In Malaysia, although there is good infrastructure, consumer is still paying with high internet charges and the online shopping behavior among the consumer is still not well-developed. People are still not willing to purchase things from the internet. This research aims to identify what is the consumer’s perception, and reason of the reluctance to use online shopping in Malaysia is lower than other countries. This research also seeks to assess why Malaysia market does not have a famous online shopping website for domestic and international market. Results of findings show that Corporate Reputation, Website Design, Fulfillment/Reliability and Security/Privacy had a significant positive relationship in building online loyalty in Malaysia, while Perceived Value shows an unstable relationship toward online loyalty, and customer service is not significant in Malaysia online shopping loyalty.